2021
DOI: 10.1001/jamanetworkopen.2021.28225
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Obstructive Sleep Apnea and Brain White Matter Hyperintensities in a Population-Based Cohort in Germany

Abstract: IMPORTANCEUnderlying pathomechanisms of brain white matter hyperintensities (WMHs), commonly observed in older individuals and significantly associated with Alzheimer disease and brain aging, have not yet been fully elucidated. One potential contributing factor to WMH burden is chronic obstructive sleep apnea (OSA), a disorder highly prevalent in the general population with readily available treatment options. OBJECTIVE To investigate potential associations between OSA and WMH burden. DESIGN, SETTING, AND PART… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 43 publications
1
20
0
Order By: Relevance
“…This suggests that OSA may promote microvascular pathology that ultimately results in cognitive impairment in the elderly, as previously postulated [ 40 ]. In support of this hypothesis, it has been shown that OSA and nocturnal hypoxaemia are associated with frontal white matter lesions [ 41 , 42 ] and morphometric changes in the deep grey nuclei [ 43 , 44 ]. In addition, it has recently been reported that neurofilament light chain (a marker of white matter integrity) increases in plasma of patients with severe OSA as a function of TST90 after CPAP withdrawal [ 45 ].…”
Section: Discussionmentioning
confidence: 95%
“…This suggests that OSA may promote microvascular pathology that ultimately results in cognitive impairment in the elderly, as previously postulated [ 40 ]. In support of this hypothesis, it has been shown that OSA and nocturnal hypoxaemia are associated with frontal white matter lesions [ 41 , 42 ] and morphometric changes in the deep grey nuclei [ 43 , 44 ]. In addition, it has recently been reported that neurofilament light chain (a marker of white matter integrity) increases in plasma of patients with severe OSA as a function of TST90 after CPAP withdrawal [ 45 ].…”
Section: Discussionmentioning
confidence: 95%
“…The fact that insomnia is associated with elevated levels of CSF NfL suggest that it may be cleared by the glymphatic system like amyloid ( Xie et al, 2013 ; Albargothy et al, 2018 ) and tau ( Iliff et al, 2014 ). The relationship between NfL and parameters of hypoxemia in OSA patients suggest a different mechanism, potentially via increased oxidative stress and neuroinflammation causing neurodegeneration ( Daulatzai, 2015 ; Snyder et al, 2017 ) and white matter disease ( Rostampour et al, 2020 ; Zacharias et al, 2021 ), which may contribute to sleepiness ( Xiong et al, 2017 ). Although tau-related neurodegeneration of wake-promoting neurons can start in pre-clinical stages of AD ( Braak et al, 2011 ; Stratmann et al, 2016 ), and could contribute to sleepiness ( Oh et al, 2022 ), it is unknown whether it could be associated with higher NfL levels.…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive neuroimaging techniques have been widely used to explore the pathophysiological mechanisms of various diseases, such as neurological and psychiatric disorders. Different neuroimaging techniques have been used to explore related structural, functional, and metabolic alterations in OSA patients ( 7 9 ). Many previous studies ( 10 13 ) using structural neuroimaging have suggested that OSA patients may have brain tissue damage.…”
Section: Introductionmentioning
confidence: 99%